Avaliação da eficiência de escolas secundárias inglesas: Abordagem de decomposição de eficiências utilizando DEA - Portela, Maria (2011)
This paper outlines a DEA based apporach to decompose overall measures of efficiency calculated at the pupil-level into those attributable to the pupil and to the school the pupil attends. Data on over 6000 UK pupils taking A-levels in 1994 were analysed firstly on a within-school basis, so that pupil efficiency could be identified, after allowing for contextual factors such as innate ability. Then, all schoold were grouped together and pupils assessed so that differences in pupil efficiencies attributable to the school attended could be identified. Efficiency measures across pupils attending the same shool were aggregated, through averages, so that conclusions concerning the average effects of the school attended on pupils attainments could be ascertained. The availability of efficiency measures at the pupil-level still enable the analysis of whether schools were differentially effective with differing groups of pupils.